Pancreas deficiency modifies bone development in the ovine fetus near term. Issue 1 (24th November 2021) - Lanham, Stuart A; Blache, Dominique; Oreffo, Richard O C; Fowden, Abigail L; Forhead, Alison J
Abstract : Hormones have an important role in the regulation of fetal growth and development, especially in response to nutrient availability in utero . Using micro-CT and an electromagnetic three-point bend test, this study examined the effect of pancreas removal at 0.8 fraction of gestation on the developing bone structure and mechanical strength in fetal sheep. When fetuses were studied at 10 and 25 days after surgery, pancreatectomy caused hypoinsulinaemia, hyperglycaemia and growth retardation which was associated with low plasma concentrations of leptin and a marker of osteoclast activity and collagen degradation. In pancreatectomized fetuses compared to control fetuses, limb lengths were shorter, and trabecular (Tb) bone in the metatarsi showed greater bone volume fraction, Tb thickness, degree of anisotropy and porosity, and lower fractional bone surface area and Tb spacing. Mechanical strength testing showed that pancreas deficiency was associated with increased stiffness and a greater maximal weight load at fracture in a subset of fetuses studied near term. Overall, pancreas deficiency in utero slowed the growth of the fetal skeleton and adapted the developing bone to generate a more compact and connected structure. Maintenance of bone strength in growth-retarded limbs is especially important in a precocial species in preparation for skeletal loading and locomotion at birth.